2008
DOI: 10.1002/anie.200803003
|View full text |Cite
|
Sign up to set email alerts
|

Frustrated Phases of Block Copolymers in Nanoparticles

Abstract: 3D confinement effect: Block copolymers form novel phase separation structures in the nanoparticles owing to frustration of the nanosized confinement effect. Whereas films of the block copolymers form lamellar structures, the nanoparticles formed unique structures (Janus‐type, tennis‐ball‐, mushroom‐, wheel‐, and screwlike structures) depending on the ratio between particle diameter and molecular weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
175
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 173 publications
(178 citation statements)
references
References 30 publications
2
175
1
Order By: Relevance
“…Figure S1 shows that the emulsion droplets had average diameter of 18.365 µm, which was approximately 3.6 times larger than the d pore value. [24][25][26][27] Next, we estimated the relationship between d droplet and d BCP using Equation [1] and compared it with our experimental observation. We assumed that the final BCP particles are perfect spheres solely composed of polymers with no residual solvent:…”
Section: Characterizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure S1 shows that the emulsion droplets had average diameter of 18.365 µm, which was approximately 3.6 times larger than the d pore value. [24][25][26][27] Next, we estimated the relationship between d droplet and d BCP using Equation [1] and compared it with our experimental observation. We assumed that the final BCP particles are perfect spheres solely composed of polymers with no residual solvent:…”
Section: Characterizationsmentioning
confidence: 99%
“…Since the densities of the polymers in PS-b-PB were 1.05 g/ml (PS) and 0.89 g/ml 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 4.5d BCP from the measured values of d droplet = 18.365 µm and d BCP = 4.366 µm, the experimental result was in excellent agreement with the calculated value. Interestingly, the relationship in Equation [1] suggested that the size of the BCP particles can be also controlled by varying c BCP .…”
Section: Characterizationsmentioning
confidence: 99%
“…We succeeded in preparing particles of various sizes from high-molecular-weight PS-b-PI, and found that unique microphase-separated structures appear in particles with D/L 0 values ranging from 1.0 to 2.1 ( Figure 11). 52 When the D/L 0 value is over 2.0, a one-directional stacked lamellar phase is observed. On the other hand, when the value is lower than 1.0, a Janus-type phase separation structure emerges.…”
Section: Block Copolymersmentioning
confidence: 99%
“…Such confinement effects have been observed within particles prepared by controlled precipitation methods, and can lead to new and useful morphologies inaccessible in bulk block copolymer systems. 151 This section of the review summarises reports where nanoscale morphology was investigated within particles from solvophobic synthesis, and/or where particles were reprocessed into microphase separated bulk materials or thin films, focussing on the influence of polymer purity on the ultimate microphase separated structure. Furthermore, a few of these reports took block copolymer materials forward for property testing, which provides insight into the effect of impurities on potential future applications.…”
Section: E Properties Of Block Copolymers From Solvophobic Synthesismentioning
confidence: 99%
“…Solvophobic block copolymer particles can be prepared by numerous techniques, which are thoroughly reviewed elsewhere, [241][242][243] including: 1) self-organised reprecipitation (SORP), in which particles precipitate upon solvent evaporation from a solution of block copolymer in a non-solvent/solvent mixture 151,244,245 ; 2) evaporation-induced self-assembly (EISA), where a polymer dissolved in a non-polar solvent is dispersed in water, and solvent evaporation leads to block copolymer self-assembly [246][247][248] ; 3) solvent evaporation from block copolymer aerosols; 4) templating within the pores of inverse opals 249 ; and 5) precipitation from a good solvent mixture into a poor solvent. 250,251 Although these routes are becoming well-established they require multiple steps, from the synthesis of block copolymer (often by anionic polymerisation)…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%